Vascular Dysfunction Induced in Offspring by Maternal Dietary Fat Involves Altered Arterial Polyunsaturated Fatty Acid Biosynthesis - Kelsall, Christopher J. (Public Library of Science, 2012)
Nutrition during development affects risk of future cardiovascular disease. Relatively little is known about whether the amount and type of fat in the maternal diet affect vascular function in the offspring. To investigate this, pregnant and lactating rats were fed either 7%(w/w) or 21%(w/w) fat enriched in either18:2n-6, trans fatty acids, saturated fatty acids, or fish oil. Their offspring were fed 4%(w/w) soybean oil from weaning until day 77. Type and amount of maternal dietary fat altered acetylcholine (ACh)-mediated vaso-relaxation in offspring aortae and mesenteric arteries, contingent on sex. Amount, but not type, of maternal dietary fat altered phenylephrine (Pe)-induced vasoconstriction in these arteries. Maternal 21% fat diet decreased 20:4n-6 concentration in offspring aortae. We investigated the role of Δ6 and Δ5 desaturases, showing that their inhibition in aortae and mesenteric arteries reduced vasoconstriction, but not vaso-relaxation, and the synthesis of specific pro-constriction eicosanoids. Removal of the aortic endothelium did not alter the effect of inhibition of Δ6 and Δ5 desaturases on Pe-mediated vasoconstriction. Thus arterial smooth muscle 20:4n-6 biosynthesis de novo appears to be important for Pe-mediated vasoconstriction. Next we studied genes encoding these desaturases, finding that maternal 21% fat reduced Fads2 mRNA expression and increased Fads1 in offspring aortae, indicating dysregulation of 20:4n-6 biosynthesis. Methylation at CpG −394 bp 5′ to the Fads2 transcription start site predicted its expression. This locus was hypermethylated in offspring of dams fed 21% fat. Pe treatment of aortae for 10 minutes increased Fads2, but not Fads1, mRNA expression (76%; P<0.05). This suggests that Fads2 may be an immediate early gene in the response of aortae to Pe. Thus both amount and type of maternal dietary fat induce altered regulation of vascular tone in offspring though differential effects on vaso-relaxation, and persistent changes in vasoconstriction via epigenetic processes controlling arterial polyunsaturated fatty acid biosynthesis.